Raising Healthy Children: Promoting a Positive Feeding Experience - Tiffany N. Stodtko; Karla P. Shelnutt; Gail P.A. Kauwell (EDIS)
All parents have heard “I don’t like that!” or “I’m not hungry!” from their child at some point or another. It’s likely that your child will not like every food that is served, but that doesn’t mean mealtime can’t still be a pleasant experience for the family. Parents may think they have sole responsibility for their child’s food choices, but Ellyn Satter, a registered dietitian who specializes in feeding and eating, advises that young children also have responsibility in the eating process. If feeding your child is stressful, read this fact sheet to learn about the division of responsibility in feeding and how to make meal times more enjoyable for the whole family. This 3-page fact sheet was written by Tiffany N. Stodtko, Karla P. Shelnutt, and Gail P.A. Kauwell, and published by the UF Department of Family, Youth and Community Sciences, December 2013.